2019
DOI: 10.1038/s41467-019-09285-9
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal microbiota and local immune response modulate the risk of spontaneous preterm delivery

Abstract: Failure to predict and understand the causes of preterm birth, the leading cause of neonatal morbidity and mortality, have limited effective interventions and therapeutics. From a cohort of 2000 pregnant women, we performed a nested case control study on 107 well-phenotyped cases of spontaneous preterm birth (sPTB) and 432 women delivering at term. Using innovative Bayesian modeling of cervicovaginal microbiota, seven bacterial taxa were significantly associated with increased risk of sPTB, with a stronger eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
362
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(382 citation statements)
references
References 40 publications
16
362
4
Order By: Relevance
“…The paucity of effective strategies for predicting and preventing PTB has led to concerted research efforts in recent years to identify and characterize biomarkers associated with preterm delivery. In parallel, the vaginal microbiome field has revealed that changes in the vaginal microbiota can precede the onset of PTB [14,18,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The paucity of effective strategies for predicting and preventing PTB has led to concerted research efforts in recent years to identify and characterize biomarkers associated with preterm delivery. In parallel, the vaginal microbiome field has revealed that changes in the vaginal microbiota can precede the onset of PTB [14,18,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy menses cease and there is a consistently elevated level of estrogen with a concomitant increase in Lactobacillus dominance (47). Several studies have suggested that altered microbiota are associated with preterm birth (48)(49)(50). Preterm premature rupture of membranes (PPROM), chorioamnionitis and early or late miscarriages have also been associated with changes in the vaginal microbiome (51)(52)(53)(54)(55)(56).…”
Section: Vaginal Microbiomementioning
confidence: 99%
“…On the one hand, high abundance of certain Lactobacillus species, but on the other hand, also a generally low abundance of lactobacilli (along with bacterial vaginosis) has been associated with PTB [11] [12]. A very recent study, however, highlighted the role of an immune-system component, namely beta-defensin-2, which was found to be negatively correlated with spontaneous PTB, largely independent of the microbiome profile assessed [13]. A causal link between vaginal microbiome composition and PTB has not been established to date.…”
mentioning
confidence: 99%